2021
DOI: 10.1071/wf20168
|View full text |Cite
|
Sign up to set email alerts
|

Bureaucratic inertia in dealing with annual forest fires in Indonesia

Abstract: Indonesia has sustained annual forest fires since the 1990s related to land clearing activities for agriculture. The Indonesian Government has made substantial efforts to resolve annual fires by improving intergovernmental coordination at national and local levels. Overall, 96 government agencies are liable for controlling forest fire. This study explores local to central government’s bureaucratic reluctance in addressing forest fires, focusing on Riau Province, the most forest fire-prone region in Indonesia. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 45 publications
1
20
0
1
Order By: Relevance
“…Since TPSP is a non-state action initiative, we also support the argument posited by Fisher et al (2020) that collaborative action works if the initiative comes from the bottom and is applied in a flexible and transactional way rather than in a top-down and rigid form of government intervention (see also Madden and McQuinn 2014). The previous research has shown the failure of top-down collaborative arrangement in dealing with forest fires in Indonesia due to bureaucratic inertia where power is centralised in vertical government institutions (Purnomo et al 2021). The evidence from our case study suggests that informal collaboration from a non-state initiative has enabled the local institution in the peatland fire mitigation.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Since TPSP is a non-state action initiative, we also support the argument posited by Fisher et al (2020) that collaborative action works if the initiative comes from the bottom and is applied in a flexible and transactional way rather than in a top-down and rigid form of government intervention (see also Madden and McQuinn 2014). The previous research has shown the failure of top-down collaborative arrangement in dealing with forest fires in Indonesia due to bureaucratic inertia where power is centralised in vertical government institutions (Purnomo et al 2021). The evidence from our case study suggests that informal collaboration from a non-state initiative has enabled the local institution in the peatland fire mitigation.…”
Section: Discussionsupporting
confidence: 79%
“…The depth of the fires in the peatland can reach 1.1 m and the underground fires produce much more smoke compared to crown fires (Ballhorn et al 2009). Moreover, previous research has shown the reluctance of bureaucracy in dealing with forest fires in Indonesia due to the centralisation of power in fire response (Purnomo et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…However, the reality is that people are less interested because of limitations on product marketing. Become a record of the government in peat restoration to assess the involvement of village governments, the availability and capabilities of community groups, assistance, monitoring and evaluation, and accountability [29]. In addition, strengthening the role of district governments is crucial in peat restoration because they can certainly know precisely the situation, environment, and socioeconomics of its people.…”
Section: Figure 3 Area Of Land Revegetated In Jambi Provincementioning
confidence: 99%
“…Community participation is essential because it is the implementer of multiple activities pursued by the Government (Schultz et al 2019). This study was conducted because forest fires have an important impact on evaluating government efforts to strengthen local institutions that deal with forest fire incidents (Purnomo et al 2021a). This research was conducted because forest fires have an important impact on evaluating the government's efforts to strengthen local institutions that deal with forest fire incidents (Purnomo et al 2021b).…”
Section: Introductionmentioning
confidence: 99%